2014
DOI: 10.1093/brain/awu318
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of TNFSF10 ameliorates functional outcome in a murine model of Alzheimer’s disease

Abstract: Alzheimer's disease is one of the most common causes of death worldwide, with poor treatment options. A tissue landmark of Alzheimer's disease is accumulation of the anomalous protein amyloid-β in specific brain areas. Whether inflammation is an effect of amyloid-β on the Alzheimer's disease brain, or rather it represents a cause for formation of amyloid plaques and intracellular tangles remains a subject of debate. TNFSF10, a proapoptotic cytokine of the TNF superfamily, is a mediator of amyloid-β neurotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 48 publications
9
74
0
Order By: Relevance
“…In fact, expression of TRAIL is increased in all these conditions, and associated with caspase activation, gliosis, and overexpression of an array of proinflammatory mediators [18]. Consistently, immunoneutralization of TRAIL results in decreased amyloid-b accumulation in the brain of 3xTg-AD mouse and reduced cognitive decline [19].…”
Section: Introductionmentioning
confidence: 83%
“…In fact, expression of TRAIL is increased in all these conditions, and associated with caspase activation, gliosis, and overexpression of an array of proinflammatory mediators [18]. Consistently, immunoneutralization of TRAIL results in decreased amyloid-b accumulation in the brain of 3xTg-AD mouse and reduced cognitive decline [19].…”
Section: Introductionmentioning
confidence: 83%
“…LTP and spatial memory impairment [50–53] were also evident. In our recent studies [54], 3XTg at 8–9 months of age showed an increase of Aβ42 levels and an increase of inflammatory mediators in the hippocampus, and an impairment of cognitive functions assessed by the MWM test and the NOR test. Increased age-related anxiety and fearfulness have been reported in some studies [5557].…”
Section: Transgenic Models For the Study Of Admentioning
confidence: 98%
“…TNF-α exerts a key role in this early proinflammatory process observed in preclinical AD as emerges from preclinical studies in animal models of AD (111)(112)(113)(114) as well as from human longitudinal studies (21,(113)(114)(115). TNF-α is chronically released during the course of AD pathology, likely by activated microglia, neurons, and astrocytes stimulated by increased levels of extracellular Aβ (111).…”
Section: Cellular and Molecular Neuroinflammatory Pathways In Alzheimmentioning
confidence: 99%